Jughead. Volume one - Zdarsky, Chip (Archie Comics Publications, Inc., 2016)
"Riverdale High prides itself on providing a quality education. But to Jughead Jones, what matters most is meal time--and Riverdale delivers solid midday chow. But when that sacred time is tampered with by a hot-headed new principal, Jughead swears vengeance! Can the burger-loving beanpole curry enough favor (see what we did there?) to rollback the cuisine catastrophe?"--Back cover.